Perancangan UI/UX pada Prototype Website sebagai Strategi Meningkatkan Penjualan Internasional dengan Menggunakan Pendekatan Design Thinking : (Studi Kasus: Brand Ourex) - Cinta Hanura Diva Firdaus (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This study aims to design an e-commerce website prototype for Ourex as a strategy to enhance international sales using the Design thinking approach. Previously relying only on social media and marketplaces, Ourex requires an independent digital platform to improve professionalism and strengthen its global competitiveness. The research was carried out through the stages of empathize, define, ideate, prototype, and test, with data collected from interviews, questionnaires, observations, and competitor analysis. The prototype was then evaluated using Heuristic Evaluation to identify usability issues and the System Usability Scale (SUS) to measure user satisfaction and comfort. The results of the Heuristic Evaluation revealed several minor issues, such as visual consistency and icon clarity, but the core functions were found to work effectively. Meanwhile, the SUS score was above the average benchmark, indicating that users experienced the prototype as easy to use, clear, and efficient. The comparison of both methods shows that the heuristic findings provide insights for detailed design improvements, while the SUS results confirm that the prototype already meets user needs overall. Thus, the Ourex website prototype has the potential to serve as a professional and competitive digital solution in supporting international sales strategies.